Sustentabilidade e a indústria de papel e celulose: uma análise dos indicadores ambientais de sustentabilidade das empresas Klabin e Suzano S.A - Bonini, Gabriela Leandra Souza (Universidade Federal de São Carlos, 2025)
Sustainability in the pulp and paper industry has gained prominence due to increasing pressure for responsible environmental practices. This study evaluates the environmental indicators of Klabin and Suzano S.A., leaders in the Brazilian sector, based on their 2023 sustainability reports. The research addresses energy consumption, water management, waste, and carbon emissions, as well as commitments related to the Sustainable Development Goals (SDGs). The main objective was to analyze the progress of environmental indicators and the disclosure and standardization of information. The specific objectives included: collecting and comparing the companies environmental indicators; evaluating the standardization of disclosed data; and examining long-term commitments and their alignment with the SDGs. The study employed a descriptive qualitative analysis based on the 2023 sustainability reports. Data were organized into spreadsheets and analyzed comparatively. Inclusion criteria considered companies featured in sustainability rankings, such as the Corporate Sustainability Index (ISE) and the Carbon Disclosure Project (CDP). The results highlighted that Klabin stood out for its progress in energy efficiency, while Suzano maintained stability and self-sufficiency in energy generation. Regarding water management, Klabin reduced consumption in water-stressed areas by 20.72%, while Suzano achieved a 99.99% reduction due to the reclassification of areas and initiatives like the Nascentes do Mucuri program. In waste management, Suzano made 90.3% progress toward its goal of reducing industrial waste sent to landfills by 70% by 2030. Klabin achieved a 99.3% total waste reuse rate, reinforcing its circular economy model. Another key topic was carbon emissions: Suzano committed to removing 40 million tons of CO₂ by 2025, while Klabin aims to capture 45 million tons by 2030. Both companies demonstrated significant advances in mitigating climate change. The analyzed companies show leadership in integrating sustainable practices into their operations. Klabin excelled in reducing water consumption and advancing renewable energy, while Suzano showed greater progress in waste management and climate initiatives. Despite the positive results, the lack of standardization in reporting methods complicates direct comparisons. The adoption of stricter national standards would enhance transparency and comparability in the sector.
Sustainability and the pulp and paper industry: an analysis of environmental sustainability indicators of the companies Klabin and Suzano S.A
Keywords: Sustentabilidade; Papel e Celulose; Indicadores Ambientais; ODS; Relatórios de Sustentabilidade; Sustainability; Environmental indicators; Pulp and paper; Sustainability reports; ENGENHARIAS::ENGENHARIA SANITARIA; 9. Indústria, Inovação e Infraestrutura